Burn Care on Cruise Ships—Epidemiology, international regulations, risk situation, disaster management and qualification of the ship's doctor. Issue 6 (September 2016) - Ottomann, C.; Hartmann, B.; Antonic, V.
Highlights: The demand for therapy of burns on board of cruise ships has increased. In the cruise ship industry it is usually a doctor with general medical training. Medical staff at sea usually have only minor surgical skills. The article provides an overview of the risks presented by a fire on board. For remote burn care at sea new training concepts for ship's doctors would be benefit. Abstract: With the increasing numbers of passengers and crew on board vessels that are becoming larger and larger, the demand for ship's doctors who can adequately treat burns on board has also increased. In the cruise ship industry it is usually those doctor's with internal and general medical training who are recruited from an epidemiological point of view. Training content or recommendations for the treatment of thermal lesions with the limited options available in ship's hospitals and where doctors with no surgical training operate do not yet exist. The guidelines recommended by the Cruise Lines International Association (CLIA) regarding medical staff have only included physicians with minor surgical skills until now. With the introduction of the ATLS ® course developed by the American College of Surgeons, the requirements for the qualification of the ship's doctor on board cruise ships shall change from January 2017. The article discusses the question of whether having completed the ATLS ® course, the ship's doctor is trained to adequately treat thermal lesions or severe burns persons on-board, and presents the current discussion on the training content for ship's doctors within the International Maritime Health Association (IMHA). It also provides an overview of existing international regulatory frameworks, the risks presented by a fire on board, the problem of treating burns victims out of reach of coastal rescue services, and alternative training concepts for ship's doctors regarding the therapy of thermal lesions on-board.